Penerapan Gaya Kepemimpinan Pada Instansi Partai Politik Golkar Provinsi Sumatera Barat - Zatillah, Rafika; Rahayu, Putri Indah; Fadhiilah, Mutiara; Raudatuljannah, Sitti (Inovan Publisher, 2024)
This research aims to examine and find out the application of leadership style in the Golkar Political Party Institution of West Sumatra Province, as well as evaluate the causes of problems that arise in the application of leadership style in the Golkar Political Party Institution of West Sumatra Province and analyze the solution in order to achieve a good leadership style in the Golkar Political Party Institution of West Sumatra Province. The focus of this research is (1) How is the application of leadership style in the Golkar Political Party Institution of West Sumatra Province (2) What are the obstacles that arise in the application of leadership style in the Golkar Political Party Institution of West Sumatra Province (3) How are the efforts made to deal with obstacles in the application of leadership style in the Golkar Political Party Institution of West Sumatra Province. This research uses qualitative research methods that utilize interview methods, observation and utilization of documents. the data used is primary data while the types of data used are interviews and observations. The results showed that the leadership style used by the leader of the Golkar Party Institution of West Sumatra Province is a democratic leadership style, but there are still several factors that inhibit the leadership style of the leader of the Golkar Party Institution of West Sumatra Province. including the lack of communication between leaders and members and between members.